2022
DOI: 10.3390/joitmc8020096
|View full text |Cite
|
Sign up to set email alerts
|

A New Stock Price Forecasting Method Using Active Deep Learning Approach

Abstract: Stock price prediction is a significant research field due to its importance in terms of benefits for individuals, corporations, and governments. This research explores the application of the new approach to predict the adjusted closing price of a specific corporation. A new set of features is used to enhance the possibility of giving more accurate results with fewer losses by creating a six-feature set (that includes High, Low, Volume, Open, HiLo, OpSe), rather than the traditional four-feature set (High, Low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…In addition, we recommend that may researchers investigate the connection between the use of social media and the performance of the stock market. The economic climate that is created by the news media or the direct observation of the stock market sentiment can be used to make decisions re- In order to prove the effectiveness of CNN-LSTM, we compared this proposed deep learning model's result with the result of [51], who also used the companies Tesla and Apple. The results of the CNN-LSTM model proposed in this study compared to the models used in [51] are shown in Table 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we recommend that may researchers investigate the connection between the use of social media and the performance of the stock market. The economic climate that is created by the news media or the direct observation of the stock market sentiment can be used to make decisions re- In order to prove the effectiveness of CNN-LSTM, we compared this proposed deep learning model's result with the result of [51], who also used the companies Tesla and Apple. The results of the CNN-LSTM model proposed in this study compared to the models used in [51] are shown in Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…The economic climate that is created by the news media or the direct observation of the stock market sentiment can be used to make decisions re- In order to prove the effectiveness of CNN-LSTM, we compared this proposed deep learning model's result with the result of [51], who also used the companies Tesla and Apple. The results of the CNN-LSTM model proposed in this study compared to the models used in [51] are shown in Table 6. The propped CNN-LSTM model is superior to the other study's models according to the MSE metric.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in natural language processing (NLP), LSTM networks are used for text generation [ 55 ], translation [ 56 ], etc. In time series data, such as stock prices and weather prediction, LSTMs can be used for analysis and forecasting [ 57 , 58 ]. Similarly, LSTMs are highly effective for the detection of anomalies in time series data [ 59 ].…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Remarkably, several studies have demonstrated the high level of accuracy of the machine learning methods [67][68][69][70], and they used these models for improving many problems. On the other hand, From the literature, most of the studies have investigated the relationship between oil prices and macroeconomic factors, but such studies seldom focus to validate the agreement on how much these macroeconomic factors influence oil prices [71].…”
Section: Literature Reviewmentioning
confidence: 99%